Suicidal behavior in persons attended in out-of-hospital emergency services in Spain - Ramos-Martín, Javier; Gómez Sánchez-Lafuente, Carlos; Martínez-García, Ana I.; Castillo-Jiménez, Pilar; Guzmán-Parra, José; Moreno-Küstner, Berta (Frontiers in Psychiatry, 2023)
The aims of this study were to describe the use of health services by patients attended for suicidal behavior by out-of-hospital emergency services and to identify the variables associated with the repetition of this behavior in Spain. Methods: An analytical, observational, retrospective study was carried out. A total of 554 patients attended by the mobile teams of the Primary Care Emergency (mt-PCES) of the Malaga Health District (Spain), after being coordinated by the 061 Emergency Coordination Center (ECC) were analyzed. Results: Of the total, 61.9% of the patients were women and the mean age was 43.5 years. Ninety-six percent (N=532) of the patients attended by mt-PCES were transferred to hospital emergency services. Regarding clinical decision, of those transferred 436 persons (82%) were discharged home. Of the total sample 25.5% (N=141) were referred to primary care, while 69% (N=382) were referred to outpatient mental health care. Regarding follow up in the 6 months after being seen by emergency services, among those referred to a mental health facility, 64.4% (N=246) attended the follow-up appointment while out of the total sample only 50.5% (N=280) attended a follow-up appointment with an outpatient mental health service. Finally, it should be noted that 23.3% presented a relapse of suicidal behavior in the 6 months following index episode. The variables associated with repetition of suicidal behavior were older age, greater number of previous suicide attempts and having any contact with mental health services in the following 6 months. Conclusions: We believe that selective suicide prevention initiatives should be designed to target the population at risk of suicide, especially those receiving both out-of-hospital and in-hospital emergency services.